Pelecehan Seksual begal Payudara, Upaya Kepolisian Resor Langsa Dalam Pencegahan Kejahatan Seksual Begal Payudara,Upaya Kepolisian Resor Langsa Dalam Penanganan Kejahatan Seksual Begal Payudara - Rahayu, Puri; Krisna, Liza Agnesta; Aldino, Hanri (Legalita, 2025)
Abstract The rampant phenomenon in Indonesia of sexual harassment, particularly breast groping, has become a serious problem in Langsa City and threatens the safety and comfort of the community. This not only causes victims to feel fear and trauma, but also makes them feel that their dignity and integrity have been violated. This study aims to examine the efforts of the Langsa Police in preventing and handling this crime. The method used is empirical jurisprudence to collect data through interviews and analysis of official documents. The results show that the police have taken various preventive measures, such as routine patrols and legal counseling through the Community Police (Bhabinkamtibmas) in Gampong-Gampong. However, major challenges remain, particularly regarding the public's reluctance to report incidents. Data shows that there are more cases of sexual abuse that go unreported, indicating that current laws are insufficient to protect victims and that efforts to date have not been enough to convince victims to come forward. The importance of this study lies in the need for advice to the police on how to deal with crimes of sexual abuse. This research is expected to provide useful insights to strengthen future prevention and legal handling efforts, considering issues such as social stigma and lack of legal knowledge among the public. Keywords: Police, Prevention, Legal Handling, Breast Mugging